2022
DOI: 10.1177/02601060221096932
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of energy and nutrient intakes among undergraduate students attending a University in the North of England

Abstract: Background: Unhealthy diets are typical of university students and are often thought to be unrepresentative of the general population. The main aim was to determine the energy and nutrient intakes of a large cohort of undergraduate university students; and to compare to gender-specific dietary reference values (DRVs) and nutrient data from the general population. Methodology: Data was collected from 639 university students aged 18–24 years who completed 4-day diet diaries. The energy and nutrient intake was de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…Nutrient intake among students varies depending on the study. One study found that undergraduate university students had lower energy intakes compared to dietary reference values (DRVs) and the general population, but their intake of protein, fat, saturated fat, and carbohydrates exceeded DRVs (41).…”
Section: Nutrient Intakementioning
confidence: 99%
“…Nutrient intake among students varies depending on the study. One study found that undergraduate university students had lower energy intakes compared to dietary reference values (DRVs) and the general population, but their intake of protein, fat, saturated fat, and carbohydrates exceeded DRVs (41).…”
Section: Nutrient Intakementioning
confidence: 99%